Підвищення ефективності сприйняття лекційного матеріалу студентами медичних вузів = Enhancement of efficiency perception a lecture material medical students - Oksana Stukan (Kazimierz Wielki University, 2015)
Stukan Oksana. Підвищення ефективності сприйняття лекційного матеріалу студентами медичних вузів = Enhancement of efficiency perception a lecture material medical students. Journal of Education, Health and Sport. 2015;5(10):299-305. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34069 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A299-305 https://pbn.nauka.gov.pl/works/670796 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 25.10.2015.   ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ СПРИЙНЯТТЯ ЛЕКЦІЙНОГО МАТЕРІАЛУ СТУДЕНТАМИ МЕДИЧНИХ ВУЗІВ ENHANCEMENT OF EFFICIENCY PERCEPTION A LECTURE MATERIAL MEDICAL STUDENTS   О. К. Стукан Oksana Stukan   ВНМУ ім.М.І.Пирогова, кафедра мікробіології, вірусології та імунології, Вінниця Vinnitsky National Medical University named M.I.Pirogova, department of Microbiology   Abstract   Microbiology is one of the basic subjects in preparation of future doctor. Without knowledge of Microbiology science is impossible to substantiate the diagnosis, treatment and prevention of infectious diseases microbiology as a basis for of all clinical and medical care disciplines. It promotes the logical perception of subjects forming clinical thinking, without which it is impossible to be an expert. Focusing on the ultimate instruction of specialist training in learning the basics of Microbiology of immunology forming in students knowledge about the role of microorganisms in human pathology; features of morphology and physiology, meaning of Infectious microbes in pathology of man, principles of microbiological, of serological diagnosis, specific prophylaxis of infectious diseases. The lecture should be read in clear language, unfamiliar words and terms to explain, do not to burden lecture of fashionable terms and foreign words. The learning process is multifaceted and multifactor activity of teacher and students it aims to implement many functions. The main purpose focusing students on this material, and no interested in difficult load terms for the next converting short-term memory to long-term. The use informative computer technology in not only increases the amount of educational material, varies its structure, finds new forms to the request, but is characterized by the ability improve the quality of by students mastering a material lectures and introduce a system new knowledge. At the department of microbiology, virology and immunology VNMU them. Pirogov educational process carried out by the credit system, the process of filing of new material in the lectures for students on specialization "clinical pharmacy" is focuses on the skills for future professionals. Clinical Pharmacist is knowledgeable of disciplines as of the pharmaceutical and clinical, laboratory profile and understands the doctor and the patient, acts as an intermediary between them. Conclusion. Modern technology lecture is able to break the stereotype that sat deep in the mind of the student, that he should "give" ready knowledge, and replace it with the understanding that he must "win" the knowledge of their own efforts. Through the use of multimedia technology capabilities creates a fundamentally new and unique research environment that promotes individual and collective creative abilities of students, formed effective communication skills in achieving a positive result in future therapeutic activity.   Keywords: microbiology, educational process, lecture, improvement of perception.   Резюме   Повышение эффективности восприятия лекционного материала студентами медицинских вузов. Современое образование предусматривает большое количество времени для студента на самообразование, куда входит как теоретическая подготовка так и практическая робота над усвоенным материалом. Лекционная форма проведения занятий была и остается главной частью вузовской підготовки и процесс начитки лекции непосредственно связан с запоминанием, хранением и воссозданием материала студентами. Сам термин "лекция" ведет происхождение от латинского "lectio", что в переводе значит чтение, а производное "lector" - чтец. Такое значение обусловленно тем, что сначала в Давней Греции, Давнем Риме, а потом и в университетах средневековой Европы основной формой работы преподавателя было откомментированное чтение текстов книг. На современном этапе лекция выступает и как метод учебы, который создает фундаментальную базу знаний студентов из дисциплины, которая предусмотрена учебным планом, и как организационная форма учебы - то есть способ интерактивного взаимодействия преподавателя и студентов. По Европейскому стандарту дипломированный специалист сразу занимает рабочее место и исполняет свои должностные обязанности, гарантией качественной работы есть диплом и авторитет высшего учебного заведения. Поэтому возникает потребность во все большей эффективности учебного процесса.   Ключевые слова: микробиология, учебный процесс, лекция, улучшение восприятия.